Mosquitoes in crabholes: A hidden realm of culicid diversity in India - Natarajan, R.; Gopalakrishnan, S.; Shriram, A.n.; Kumar, Ashwani (Zootaxa, 2024)
This is the first listing of mosquitoes inhabiting crabholes across the diverse landscapes of India. Drawing from an extensive review of existing literature on mosquito diversity in various ecological regions of the country, the adults or immature stages of 68 mosquito species have been found in crabholes. This entomological assessment revealed that 24 species occur in crabholes in mangroves, characterized by brackish water, while an additional 44 species are found in freshwater crabholes in forested areas. The majority of the species appear to have been collected as resting adults, a pattern consistent with earlier observations. The implications of this finding highlight the complex relationship between mosquitoes and their association with crabholes. This new knowledge opens up avenues to future studies that explore the diversity and biology of mosquitoes in these unique habitats.